SEMIOTICS OF WAYANG GOLEK LINGKUNG SENI GIRIHARJA'S SHOW AS A LEARNING SOURCE OF CIVIC EDUCATION - Abdul Aziz; Kokom Komalasari; Iim Siti Masyitoh (Universitas Negeri Malang, 2017)
Abstract: Currently Civic Education learning in schools is still teacher centered learning. Consequently, the output of the study only focused on strengthening the aspects of knowledge (civic knowledge) students only. This research aims to provide an alternative learning civic education with student-centered learning methods, through the semiotics of Wayang Golek Lingkung Seni Giriharja as a learning resource. The research method used ethnography with a qualitative approach. The results showed that semiotics Wayang Golek Lingkung Seni Giriharja can be maximized as a learning resource civic education in citizenship competencies development of student. They will be active to dig semiotic values contained on the Wayang Golek Lingkung Seni Giriharja by means of learning material to link that is being discussed DOI : http://dx.doi.org/10.17977/um019v2i22017p091